Ajaran Pendidikan Anti Korupsi ibnu Athaillah (Menggali Nilai Pendidikan Moral-Sprititual dari Sebagian Untaian Hikmah Kitab Al-Hikam) - Rahem, Zaitur (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2017)
Corruption here has been ingrained. From year to year, the number of corruption continue to grow. Spread out to various corners of the bureaucracy and social status. Some movement of the Government and tactical systemic organs do. Eradication and the fight against corruption as no betaji. Therefore, one captured, grew so many actors who perform the same action. Back to the sociological typology of Indonesian society, corruption is contrary to the cultural roots of our ancestors. Corruption odds for causing corruption in various aspects of life in Indonesia. There are so many people get hurt and become victims of corrupt practices. Perhaps, therapy metaphysical version of Ibn 'Athaillah through counsels Al-Hikam bidder will be octopus of corruption in Indonesia. At least, this wisdom can be banged strands of consciousness and the hearts of all elements of the Indonesian nation.